Mothers' experiences of caring for children receiving growth hormone treatment - ALSAIGH, RASHA (Trinity College Dublin. School of Nursing & Midwifery. Discipline of Nursing, 2019)
The last five decades has seen a rapid expansion in the number of children requiring growth hormone treatment (GHT). Children generally begin GHT at a very early age which means parents often endure a complex and difficult pathway with regards to GHT decision making, administration, storage, medication adherence and costs. The literature revealed parents lack of choice in GHT devices, lack of support, lack of adherence, lack of reassurance about side effects, and organisational difficulties including; preparation, administration, storage and travel. Parents have significant responsibilities, yet there are no studies which reflect an empirical understanding of the essence of parents’ experiences of caring for their child requiring GHT. The life-world of the parent that consists of social, practical, and taken-for-granted dimensions are largely unknown and therefore there was scope for this study. The aim was to explore parents’ day to day experiences, the ‘taken for granted’ aspect of caring for children receiving GHT. This study used the philosophy of hermeneutic phenomenology based on the approach of Gadamer. Sixteen mothers from the Republic of Ireland participated and the data were collected through in depth interviews and diary recordings. Sixteen in depth interviews and eight diaries were completed. The mothers’ experiences of caring for their child receiving GHT were framed by three concepts that were: uncertainty, normalisation and stigma. These concepts were used to elaborate on the four major meanings encapsulating their experience of caring for their children receiving GHT. The four major meanings of their lived experiences which are explained in the form of themes are: (1) ‘It’s the right thing to do’ Striving for the security and the wellbeing of the child, (2) ‘Doubting yourself constantly’ Constant uncertainty, (3) ‘But then you just get used to it I suppose’ Adhering to GHT and lifestyle changes - the new normal, (4) ‘I hadn’t been told anything about it’ Information behaviour; looking for normality and certainty. Mothers experienced significant challenges coping with the uncertainties associated with GHT. The felt stigma of restricted growth, rare medical condition and GHT appeared to hinder some mothers from seeking support from their families, other parents and communities. In addition, the substantial need for information and support was noted. These findings indicate that healthcare professionals and policy makers need to ensure that services for these children include the necessary supports for parents.
APPROVED
Keywords: Perceptions; Mothers; Phenomenology; Experiences; Growth hormone therapy; Growth hormone treatment